A pentapeptide signature motif plays a pivotal role in Leishmania DNA topoisomerase IB activity and camptothecin sensitivity - Prada, Christopher F.; Álvarez-Velilla, Raquel; Diaz-González, Rosario; Prieto, Carlos; Pérez-Pertejo, Yolanda; Balaña-Fouce, Rafael; Reguera, Rosa M. (Biochimica et biophysica acta, 2012)
Leishmania donovani – the causative agent of visceral leishmaniasis – has several evolutionary characteristics that make the disease difficult to combat. Among these differences, a rare heterodimeric DNA topoisomerase IB has been reported thus opening a new promising field in the therapy of leishmaniasis. Several studies of the human enzyme have pointed to the importance of the linker domain in respect to camptothecin sensitivity. At present, it has been impossible to pinpoint the regions that make up the linker domain in Leishmania. Several site-directed mutations as well as internal and linear truncations involving both subunits were assayed on both, relaxation activity and sensitivity to camptothecin. Truncations performed on the trypanosomatids conserved motif (RPPVVRS) of the small subunit of leishmanial DNA topoisomerase IB demonstrated that elimination of pentapeptide RPPVV produced a nonfunctional enzyme. However, the removal of the dipeptide RS led to an enzyme with reduced relaxation activity and less sensitivity to camptothecin. The basic structure, both sensitive to camptothecin and able to fully relax DNA, composed of amino acids 1–592 and 175–262 in the large and small subunits, respectively. It has been established that the region between amino acids 175 and 180 (RPPVV) of the small subunit plays a pivotal role in both interaction with the large subunit and sensitivity to camptothecin in Leishmania. The present report describes a functional analysis of the leishmanial DNA topoisomerase IB regions directly involved both in sensitivity to poisons and in the conformation of the linker domain. [Display omitted] ► We have performed a functional analysis of leishmanial DNA topoisomerase IB. ► Constructs were assayed on relaxation activity and sensitivity to camptothecin. ► Amino acids 175 to 180 of the small subunit play a pivotal role in enzyme activity. ► RPPVV pentapeptide motif is responsible for CPT sensitivity in the small subunit.